Fire Eaters: Exploring Consumer Preferences for Labeling Extensive Livestock Products Providing Wildfire Prevention Services - Emma Soy-Massoni; Kathleen Uyttewaal; Núria Prat-Guitart; Elsa Varela (Land, 2022)
Extensive livestock grazing has proved to be a valuable tool to reduce wildfire risk in Mediterranean landscapes. Meat from herds providing wildfire prevention services exhibit sustainability traits that can appeal to ethical consumers and find a suitable niche in local markets. This study assesses the preferences of a consumer sample in the province of Girona (north-eastern Spain) for different lamb meat labeling options from herds providing wildfire prevention services. The aim is to disentangle consumer profiles, providing evidence for improved product labeling. This may increase the added value and the viability of small farms providing this service. Employing a latent class modeling approach, we explore how meat consumption patterns and socioeconomic features may contribute to explain preferences for different meat labeling options. Our results have identified three consumer profiles: traditional rural consumers relying on trust with producers, younger consumers more akin to new labeling schemes, and urban consumers that support local butchers as a trusted information source. Different labeling mechanisms may work in a complementary way to arrive to different audiences of potential consumers. Geographical indication labels can serve as a good departure point, complemented with information cues on environmental factors related to wildfire protection.